Byzantine Resilient Protocol for the IoT - Frohlich, Antonio Augusto; Scheffel, Roberto Milton; Kozhaya, David; Verissimo, Paulo Esteves (IEEE internet of things journal, 2019)
Wireless sensor networks (WSNs), often adhering to a single gateway architecture, constitute the communication backbone for many modern cyber-physical systems (CPSs). Consequently, fault-tolerance in CPS becomes a challenging task, especially when accounting for failures (potentially malicious) that incapacitate the gateway or disrupt the nodes-gateway communication, not to mention the energy, timeliness, and security constraints demanded by CPS domains. This paper aims at ameliorating the fault-tolerance of WSN-based CPS to increase system and data availability. To this end, we propose a replicated gateway architecture augmented with energy-efficient real-time Byzantine-resilient data communication protocols. At the sensors level, we introduce fault-tolerant trustful space-time protocol, a geographic routing protocol capable of delivering messages in an energy-efficient and timely manner to multiple gateways, even in the presence of voids caused by faulty and malicious sensor nodes. At the gateway level, we propose a multigateway synchronization protocol, which we call ByzCast , that delivers timely correct data to CPS applications, despite the failure or maliciousness of a number of gateways. We show, through extensive simulations, that our protocols provide better system robustness yielding an increased system and data availability while meeting CPS energy, timeliness, and security demands.